Overload Prevention in an Autonomous Microgrid using Battery Storage Units - Goyal, M.; Ghosh, Arindam; Shahnia, Farhad (Institute of Electrical and Electronics Engineers (IEEE), 2014)
A new control strategy for smooth transition of a battery storage unit (BSU) is proposed in this paper to prevent overloading in an autonomous hybrid microgrid. The BSU is controlled to come online to prevent overloading to the distributed generators (DGs) in the autonomous microgrid and to go offline when the load demand is less than the total rating of the DGs in the microgrid. The microgrid can contain either inertial DG or non–inertial DGs, which are controlled in a frequency droop. The sensing of switching on and switching off of the BSU depends on the frequency signal, which is developed in the paper. The proposed strategy is validated through PSCAD/EMTDC simulation studies.